RESPONSE OF GROWTH AND YIELD OF SOYBEAN PLANTS TO COMPOSITION OF PLANTING MEDIA AND APPLICATION OF LIQUID ORGANIC FERTILIZER: RESPON PERTUMBUHAN DAN HASIL TANAMAN KEDELAI TERHADAP KOMPOSISI MEDIA TANAM DAN PEMBERIANPUPUK ORGANIK CAIR - Ruhalena Wilis; Ella Frisella; Nurlia Farida; Delizar Nuor (PT. ROCE WISDOM ACEH, 2026)
This study aims to determine the growth and yield response of soybean plants to the composition of the planting medium and the application of liquid organic fertilizer, as well as the interaction between these two factors. The study was conducted in Neuheun Village, Mesjid Raya District, Aceh Besar Regency, Aceh Province, from July to September 2024, at an altitude of approximately 9.7 meters above sea level. The materials used included manure, burnt rice husks, compost, liquid organic fertilizer (LOF), Anjasmoro variety soybean seeds, and 40 cm x 50 cm polybags. The tools used included hoes, soil sieves, watering cans, hand sprayers, stationery, scales, calipers, and meters. The study found that the composition of the planting medium had a highly significant effect on plant height at 25, 35, and 45 days after planting. Still, they had no significant effect on stem diameter at 25, 35, and 45 days after planting. The composition of the planting medium had a significant impact on the number of productive branches at 35 days after planting, but had no significant effect on the number of productive branches at 25 and 45 days after planting, or on the weight of 100 dry seeds per plant. Liquid organic fertilizer had a highly significant effect on plant height at 35 DAP and a substantial impact at 25 and 45 DAP. However, liquid organic fertilizer had no significant effect on stem diameter, the number of productive branches at 25, 35, and 45 days after planting, or the weight of 100 dry seeds per plant.